A Rare Case of Congenital Ocular Dermoid and Acute Corneal Hydrops in a Calf - Rani, R Uma; Jagatheesan, P N Richard; Sowbharenya, , C; Arun, R; Palanivel, N (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A 10 days old Jersey cross breed female calf was brought with the complaints of epiphora, and unusual mass in right eye since birth. On clinical and slit lamp biomicroscopic examination the case was diagnosed as congenital ocular dermoid on the ventral cornea, limbus and bulbar conjunctiva extending upto the inner canthus of right eye in association with acute corneal hydrops (ACH). Under xylazine sedation, retrobulbar, supra orbital and auriculopalpebral nerve blocks, the dermoid was surgically removed and the ACH was treated successfully with appropriate medicine and temporary tarsorrhaphy. The ocular dermoid was confirmed on histopathological examination.